Aplikasi Jenis Kompos dan Dosis Pupuk NPK Terhadap Pertumbuhan dan Hasil Kedelai di Entisol Bengkulu - Hesti Pujiwati; Atra Romeida; Widodo Widodo; Dotty Suryati; Prasetyo Prasetyo; Wuri Prameswari; Wahyu Hidayat; Edi Susilo (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2023)
Soybeans can be cultivated in Entisol. However, soybean cultivation on Entisol land has problems, including low soil fertility. Providing compost and NPK is an alternative to overcome this. The research objective was to determine the best type of compost and NPK fertilizer dosage for soybean growth and yield in entisol. The research has carried out in the Entisol Bengkulu field from August to November 2020. The research design used a Complete Randomized Block Design (CRBD) with 2 factors including: the type of compost organic fertilizer consisting of: P1 = Widelia trilobata, P2 = Tithonia diversivolia, P3 = oil palm empty bunches, and P4 = Eichhornia crassipes and the NPK fertilizer dosage consisting of: N0 = 0 kg ha-1, N1 = 150 kg ha-1, N2 = 300 kg ha-1, N3 = 450 kg ha-1. Observation variables include plant growth and yield and supporting observations which include the results of initial soil analysis and climate data during the study. The results showed that NPK dosing had a significant effect on the variables of plant height, number of leaves, number of branches, root wet weight per plant, and dry weight per plant. However, the application of compost did not significantly affect all variables. Meanwhile, there was no interaction between the application of compost types and NPK dose on the growth and yield of soybean in entisols. The application of compost types and NPK fertilizer doses up to 450 kg ha-1 has not improved the growth and yield of soybeans in entisol fields.